Demographic transition and transition of urban water consumption in Brazil - Carmo, Roberto Luiz do (2014)
In this paper we discuss that, although the volume of the population is an important aspect to be considered in the relationship between population and environment, there are other factors that may be even more important. From a demographic perspective, for example, details such as composition and spatial distribution of the population are essential. In environmental terms, the style of development and level of consumption are crucial. Brazil is going through a time of important transitions. On the one hand, the demographic transition (decreased levels of mortality and birth rates), is characterized by the rapid decline in total fertility rate, from about 6 children per woman in the 1960s to fewer than 2 children per woman in the late 2000s. On the other hand, there is a consumption transition also incourse, discussed here in the relationship between improving the economic situation and increased water consumption, which is caused by the expansion of the supply system in urban areas and by the trend toward growing per capita consumption. Thus, while there has been a significant decrease in population growth rates, water consumption tends to increase as the result of changes in access patterns and consumption levels.